Photobioreactor Design for Polyhydroxyalkanoate Production Using Anoxygenic Photoheterotrophs: A Review - Sultan Shaikh (19256497) (2023)
This review paper provides an overview of various types of photobioreactors (PBRs) that could be used for the production of polyhydroxyalkanoates (PHAs) using anoxygenic photoheterotrophs, with a focus on the design and operation of these systems. The paper highlights the potential of different PBRs based on reactor geometry and growth mode, and also examines the advantages and disadvantages of each PBR type and summarizes their suitability for PNSB-PHA production. The optimization of reactor design and operation is crucial for maximizing PNSB growth and PHA productivity. The self-immobilization of bacteria in granular sludge is a promising technology for wastewater treatment and the production of PHAs, while grooved-surface PBRs and porous-substrate PBRs have limitations due to difficult biomass harvesting in the former and the presence of aerobic conditions incongruent with PNSB culturing in the latter. Limitations exist with all solutions for maximizing rapid growth and maintaining high biomass concentrations due to the requirements of phototrophic growth. Other Information Published in: Fermentation License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/fermentation9080778